PERANAN DEWAN KEHORMATAN DAERAH DAN MAJELIS PENGAWAS DAERAH TERHADAP PENEGAKAN KODE ETIK NOTARIS DI KABUPATEN BANTUL - Permatasari, Mahdiati Fauziah ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Research on the Role of the Honorary Board and the Regional Council Regional Trustees Code Enforcement Againts Notary in Bantul District Council aims to determine the position of Regional Trustees and Honorary Regional Council in monitoring the enforcement of codes of ethics Notary in Bantul and to find out what code enforcement efforts by the Board of notary Honorary Local and Regional Supervison Council in Bantul. The research is a normative juridical research is research that focuses on the research literature is normative studies which include the principles of law, principles existing laws and regulations, and to complement data obtained from the research literature conducted field research interviews conducted by the author relate to several sources. The results of this study may give a descriptive analytical nature. Descriptive because of the results of this study can be thoroughly and systematically describe the general principles of law, law principles and regulations, and be analytical because it is through this research are expected to obtain a systematic, factual and accurate information about certain facts. Based on the interview is concluded that : 1) Status of MPD higher than DKD due to the obligation to report on violations of the code of conuct that occurred to the MPD. DKD reserves the right to impose sanctions only associated with membership in an organization notary, while MPD is only entitled to a hearing regarding an alleged violation of code of conduct and a violation UUJN. It causes both a supervisory institutions do not have power and authority. 2) The efforts undertaken to DKD and MPD in the Notaries Code Bantul Regency has a maximum, which has been carrying out the duties and authority according to the code of ethics that can not be solve solely by DKD, socialization of all notaries in the district of Bantul on the importance of adherence to the Code of Ethics and UUJN, and often hold discussins and exchange ideas with Regional Board and all members in Bantul.